2012
DOI: 10.1108/01604951311322011
|View full text |Cite
|
Sign up to set email alerts
|

The Zombie Library: books reanimated via QR codes

Abstract: Purpose -This article aims to provide a comprehensive step by step plan on creating a Zombie Library, a physical collection of e-books through the use of QR codes. Drawing on the collective authors' experience working with the QR codes creation, this article aims to help librarians interested in promoting e-book collections and creating QR-coded Zombie books in their libraries. Design/methodology/approach -A literature review was performed using library databases, as well as consulting various online library s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Surprisingly, interviews of 25 academic librarians showed that none had a formalized marketing strategy for e-book promotion, although 19 noted that it is needed. 4 Some ideas to promote the collection include prominent links from the library's home page, inclusion of e-book titles in the library's catalog, full text search available via a federated search engine, faculty members alerting students, instructional sessions, creation of posters, and placement of dummy print books on the shelf to highlight online availability of a newer version.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, interviews of 25 academic librarians showed that none had a formalized marketing strategy for e-book promotion, although 19 noted that it is needed. 4 Some ideas to promote the collection include prominent links from the library's home page, inclusion of e-book titles in the library's catalog, full text search available via a federated search engine, faculty members alerting students, instructional sessions, creation of posters, and placement of dummy print books on the shelf to highlight online availability of a newer version.…”
Section: Introductionmentioning
confidence: 93%
“…Idaho State University libraries created a ''Zombie Library'' by labeling book dummies with the title, call number, and a QR code linking to books included in the Gale Virtual Reference library, as these e-books had stable URLs for individual titles and an unlimited user license. 19 Finally, Bournemouth University included QR codes in their print collection in call number ranges where students would most likely be looking for print books, as determined by reviewing reading lists. The codes link to a pre-generated search in the online catalog for e-books on a subject area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Zombie Library project at Idaho State University comes closest to directly incorporating the digital collection into the physical stacks by creating dummy books with covers, titles, call numbers, QR codes, and bibliographic information. While they experienced little use during the study period, only the reference collection was included and summaries or table of contents were not placed on the dummies (Semenza, Koury, & Gray, 2013).…”
Section: Marketing E-resourcesmentioning
confidence: 99%